Feasibility, acceptability and sustainability of postpartum contraceptive implant provision by midwives in NSW public hospitals. Issue 5 (September 2022) - Botfield, Jessica R.; Tulloch, Melanie; Contziu, Hannah; Wright, Sarah M.; Phipps, Hala; McGeechan, Kevin; Bateson, Deborah; Black, Kirsten I.
Abstract: Background: Repeat pregnancy in the first year after a birth is common. Many of these conceptions are unintended and may be prevented by providing access to contraception in the immediate postpartum period. Midwives in the hospital setting could potentially play a greater role in improving postnatal contraception information and provision. Aim: We sought to implement and examine the success of a program training hospital-based midwives in immediate postpartum implant insertion. Methods: This mixed methods study in two hospitals in New South Wales sought to explore the feasibility, acceptability and sustainability of a program that provided competency-based implant insertion training for midwives. The study documented training completion, implant insertion numbers and experience, and conducted end of study interviews with midwives and stakeholders. Findings: Twenty-seven midwives undertook training and inserted 265 implants during the study period. Interviews with 13 midwives and 11 stakeholders concluded the program to be feasible and acceptable with midwives reporting high satisfaction from their involvement. All interviewees felt that midwives were well placed to insert implants, and reported that challenges around workload and opportunities for practice were generally manageable. It was recognised that sustainability of the program would require supportive policy and regular insertion opportunities. Conclusions: Midwives successfully upskilled in implant insertions and there was widespread support for the program with expectations it would be sustained. Provision of contraceptive information and implant insertion by midwives in the immediate postpartum period is likely to increase contraceptive choice and access for women and contribute to reducing rapid repeat pregnancies.